A stable isotope record of late Quaternary hydrologic change in the northwestern Brooks Range, Alaska (eastern Beringia). (21st September 2021) - King, Amanda L.; Anderson, Lesleigh; Abbott, Mark; Edwards, Mary; Finkenbinder, Matthew S.; Finney, Bruce; Wooller, Matthew J.
ABSTRACT: A submillennial‐resolution record of lake water oxygen isotope composition (δ 18 O) from chironomid head capsules is presented from Burial Lake, northwest Alaska. The record spans the Last Glacial Maximum (LGM; ~20–16k cal a bp ) to the present and shows a series of large lake δ 18 O shifts (~5‰). Relatively low δ 18 O values occurred during a period covering the LGM, when the lake was a shallow, closed‐basin pond. Higher values characterize deglaciation (~16–11.5k cal a bp ) when the lake was still closed but lake levels were higher. A rapid decline between ~11 and 10.5k cal a bp indicates that lake levels rose to overflowing. Lake δ 18 O values are interpreted to reflect the combined effects of changes in lake hydrology, growing season temperature and meteoric source water as well as large‐scale environmental changes impacting this site, including opening of the Bering Strait and shifts in atmospheric circulation patterns related to ice‐sheet dynamics. The results indicate significant shifts in precipitation minus evaporation across the late Pleistocene to early Holocene transition, which are consistent with temporal patterns of vegetation change and paludification. This study provides new perspectives on the paleohydrology of eastern Beringia concomitant with human migration and major turnover in megafaunal assemblages.